Acute Colonic Variceal Bleeding in a Cirrhotic Patient Treated by Modified Balloon-occluded Retrograde Transvenous Obliteration: A Case Report - Ahmad L. F. Yasin; Rahil Hussein Kassamali; Mohammad Khader; Omran Almokdad; Ali Raza Barah; Ahmad Omar (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Colonic varices are an uncommon type of ectopic varices that can occur due to underlying liver cirrhosis and portal hypertension. They form a very rare cause of lower gastrointestinal bleeding that can result in massive hemorrhage. We present a 38-year-old woman with a background of ulcerative colitis complicated by primary sclerosing cholangitis-induced liver cirrhosis presenting with fresh rectal bleeding. The colonoscopy failed to identify the source of bleeding. Then, computed tomography scan showed multiple dilated tortuous venous collaterals around the descending colon that extended into the colonic submucosa and drained via the left ovarian vein representing colonic varices. She underwent balloon-occluded retrograde transvenous obliteration (BRTO), which successfully embolized these varices with no significant complications. Despite there being no established management guidelines for colonic variceal bleeding, BRTO is a minimally invasive procedure that can be considered as good option for the treatment of these varices, especially when other alternatives are not applicable.